The cult of the Horatian ode in the nineteenth century - Leedham-Green, E; Elisabeth Leedham-Green (1970)
﻿ Throughout the earlier part of the nineteenth century Vergil, Homer and Horace dominated the teaching in public schools. At Eton a boy would go through the odes two or three times at least, and would be expected to memorise them all. The handing down of interleaved texts and an unimaginative adherence to traditional systems of 'calling up' boys exempted the idle from industry or cerebration; at the same time, the knowledge of Horace acquired by a tolerably conscientious boy would probably need little enlargement to satisfy Oxford examiners, at least till the late 'fifties, though in Cambridge some familiarity with Bentley's edition would probably be required. Horace's metres were analysed by James Tate with some skill, but his paper received little attention, and most copies of Latin lyrics shew only a rudimentary knowledge of the demands of metre and vocabulary. The level at which the discussion of Horace was carried on throughout the century is demonstrated by articles in the Quarterly Review by James Hannay, novelist and essayist v in October 1333, and by Arthur Palmer, editor of the Satires, in October 1894. Horace's character is conflated from references in his works accepted with exaggerated credulity; even when the ladies of the odes are declared not to have had a real existence, Horace's attitude towards them is still discussed. Palmer and his contemporaries read and discussed the Horatian scholarship produced on the continent; Verrall and Sellar contributed to it; but new interpretations had little effect on the 'cult'. In the 'seventies William Cyples wrote two articles on Horace, in the first and most important of which he argues that the odes are virtuoso literary performances and have no basis in foot or factual morality. The articles are worth recalling for their energy, freshness and originality. By providing a contrast they reveal the general narrowness of contemporary Horatian discussion and the possibility of worshipping Horace without conforming to the cult. The characteristics of Horace and his poetry most popularly pondered are illustrated in many essays, reviews and prefaces to translations. The themes vary less than the distribution of emphasis among them. Horace's politics, philosophy and religion were discussed at much the same length as his preference for town or country. Most of his admirers supposed him to prefer the country. Disagreement was rather as to the relative importance of Horace's references to himself than as to their objective truth. Comparisons with Burns and Béranger, and with Thackeray, characterise the Horace of the nineteenth century as he usually appeared. The question of how best to translate Horace was widely debated. The flaccid 'Augustan' octosyllables of Francis were imitated by lesser translators early in the century, but they also gave rise to more self-consciously 'classical' attempts which endeavoured to demonstrate the foreign qualities of Horace's poetry. Others at the same time strove after 'popular' effects and English poetry. Every position between the two extremes is represented. Conspicuous among the 'alienists' were those who tried to write Englian verse in classical metres; some anxious to produce a more Horatian Horace, others simply using him as a conveniently fertile source of metrical variety. The difficulty of writing classical verses in English is obviously due to the different natures of Latin and English prosody. Unfortunately no analysis of the structure and dynamics of English verse has ever achieved universal acceptance. The nineteenth century experimenters encountered an additional difficulty in that they rarely agreed with one another as to how Latin verses ought to be read. The dispute was carried on with great liveliness and some ingenious solutions were suggested. Others contented themselves with forming or adapting verses on English 'rules' to serve the special needs of Horace. The first to attract much attention was Francis Newman, who set out to translate Horace in 1853 on principles similar to those which he later brought to his Iliad. In his translation of Horace the qualities which he hoped to convey were terseness and a strict adherence to the stanzaic economy of the originals. He employed rhymeless stanzas made up of iambic or trochaic lines, but fell short of elegance. Occasional successes are surrounded by passages clumsy, obscure and bizarre. His anxiety to instruct is emphasized by his decision to present the odes in a possible chronological order. The educational advantage of this scheme with reference to the 'historical' odes is self-evident, but since Newman refused to regard the 'literary houris' as fictitious, he fell into some confusion in his attempts to ascertain the order of Horace's amours. His notes on the odes sometimes reflect very strikingly his preoccupation with the political and social morality of his own times. Seven years later Theodore Martin published a complete translation of the odes. He was a prolific translator, and his Horatian activities extend from the appearance of a few versions in 1845 to a translation of Horace's complete works, accompanied by a lengthy critical biography in 1881. His aims were almost precisely opposite to those of Newman, whose translation, though it probably did not provoke Martin's, was there subject to some gentle mockery. Martin's versions are fluent and facile, recalling both to his hostile and his favourable critics the ballads of Tom Moore. They are unusual in so far as they present the odes as coherent wholes, rather than as sets of stanzas uncertainly related. The results may be a more than usually comprehensible English poem, but the intention of Horace is necessarily often distorted. The evolution of Martin's Horace over the next twenty years is influenced by the suggestions of critics, the rivalry of Conington's translation, and the translator's increasing social and literary eminence; it became something of a popular classic, a position challenged only by Conington. Conington's version which appeared in 1863, was more austere and more calculated to appeal to scholarly critics. Like Martin's it was executed in accepted English rhyming metres; like Newman's it presents, for the most part, only one English equivalent for each Latin metre. It appears that Conington took to translation as a deliberate attempt to resolve the tension between the lure of philological abstraction and a desire for a wider field of human contact. On a simple level the translation reflects this. Bven if not eminently representative of Horace, Conington's versions are more classical than Martin's: if they are rarely brilliant, they are as rarely offensive. All succeeding nineteenth century translations were liable to comparison with Conington's and it was highly praised by Quiller Couch and by Housman. Lord Lytton's translation, published in 1869, probably owed the critical attention it received largely to the fame of the author. It was undertaken originally for therapeutic purposes when Lytton's matrimonial infelicity erupted spectacularly into publicity. It has been justly described as the moat ambitious of failures in this field. Attempting to produce a version more classical than Conington's, Lytton chose, like Newman, to employ rhymeless metres; on the other hand, he allowed himself a greater degree of freedom in using more than one representative for the sapphic and the alcaic. His metres are sometimes difficult to read and probably seemed stranger to his contemporaries than they do now. By compromising Lytton failed to satisfy both those who looked for pleasant English verses and those who hoped for more servile classical approximations. As a piece of literature Gladstone's translation of Horace, executed in his eighty-fourth year, has little to recommend it either on the grounds of success or of novelty. He employed rhyming stanzas and aimed, above all, at conciseness. He is often clumsy, often Obscure and not infrequently in error. The interest of the translation lies In the circumstances in which it was made. It was initiated at the beginning of Gladstone's last electoral campaign and completed in March 1894 on the day of his formal resignation. He decided to translate Horace because his deteriorating eyesight made reading difficult, and in this employment he thought he could rely to some extent on his memory. This explains some of his mistranslations. The order in which he translated the odes, with the departures from a purely systematic progress due presumably to preference, may be ascertained from MSS preserved in the British Museum. These MSS also contain considerable passages of prose, apparently intended as prefaces to publications realised and unrealised. These I have transcribed. They supply a much more comprehensive account of Gladstone's opinion of Horace, and of his principles of translation, than anything he published, and they also include attempted justifications of a number of the practices for which his critics took him to task. I have considered, perhaps at too great length, the educational and literary backgrounds of the five translators chosen, in an attempt to place their Horatian labours in some sort of perspective with their demonstrable inclinations and total achievements. The bibliography is necessarily highly selective.